CURRENT RATIO, RETURN ON ASSET, DAN DEBT TO ASSET RATIO PADA FINANCIAL DISTRESS : BUKTI PERUSAHAAN PROPERTY, REAL ESTATE, DAN KONSTRUKSI BANGUNAN - Yuaniko Paramitra (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to examine the influence of Current Ratio, Return On Assets, and Debt To Asset Ratio on Financial Distress, in property, real estate, and building construction companies listed on the Indonesia Stock Exchange during the 2019-2020 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 99 data. Data collection with documentation and data processing with t test, f test, and test the coefficient of determination of multiple linear regression using the classical assumption test. The results of the study show that the Current Ratio has no effect on Financial Distress; Return On Assets has no effect on Financial Distress; Debt To Asset Ratio has a negative and significant effect on Financial Distress; Current Ratio, Return On Assets, Debt To Asset Ratio has no effect on Financial Distress. Recommendations for further research can use other sectors that have phenomena leading to bankruptcy, using variables other than financial ratios such as good corporate governance and free cash flow as factors that have a greater possibility of explaining bankruptcy.